Production of regeneration valaciclovir hydrochloride is with palladium -carbon catalyst's device - YANG ZHISHENG; LI YUEHUI; LI XIAOFENG (2018)
The utility model provides a production of regeneration valaciclovir hydrochloride is with palladium -carbon catalyst's device, including reation kettle, its discharge gate is connected to the filter,is equipped with feed inlet, the import of first lotion, the import of second lotion, first filtrate (liquid and second filtrate (liquid on the filter, its first lotion access connection methanol storage tank, second lotion access connection sodium formate storage tank, the device should include a filtrate collection tank and the 2nd filtrate collection tank. The utility model discloses a set upthe import of first lotion, the import of second lotion to dispose methanol storage tank and sodium formate storage tank respectively, adopt methyl alcohol and sodium formate to wash palladium -carboncatalyst, can be fine regenerate. 本实用新型提供种再生盐酸伐昔洛韦生产用钯碳催化剂的装置，包括反应釜，其出料口连接至过滤器，过滤器上设有进料口、第洗液进口、第二洗液进口、第滤液出口及第二滤液出口，其第洗液进口连接甲醇储罐，第二洗液进口连接甲酸钠储罐；该装置该包括第滤液收集罐和第二滤液收集罐。本实用新型通过设置第洗液进口、第二洗液进口，并且分别配置甲醇储罐和甲酸钠储罐，采用甲醇和甲酸钠对钯碳催化剂进行洗涤，能够很好的